Pengaruh Fasilitas Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Prestasi Kerja Pegawai Pada Diskominfo Kota Tasikmalaya - Ramdan, Muhamad; Yusnita, Rita Tri; Lestari, Suci Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine and analyze the extent to which work facilities, work discipline, and work motivation contribute to improving employee work performance at the Communication and Informatics Office of Tasikmalaya City. The research method used is a survey method with a quantitative approach. The types of data used include primary and secondary data, while the sampling technique is carried out by census of all employees of the Communication and Informatics Office of Tasikmalaya City. Data analysis uses multiple regression to test the simultaneous and partial effects of independent variables on the dependent variable. The results of the study prove that work facilities, work discipline, and work motivation together have a significant effect on employee work performance. Furthermore, partial analysis also shows that each variable, namely work facilities, work discipline, and work motivation, has a significant effect on employee work performance.